The Syndrome of Academic Burnout Experienced by Graduate Psychology Students. The Stress Factor - GAVRILI, Anastasia; VLASTOS, Dimitris D.; THEOFILOU, Paraskevi (Journal of Research in Educational Sciences, 2024)
The aim of the study was to investigate the burnout syndrome experienced by postgraduate psychology students and the role of stress. 101 graduate level psychology students participated in the study. This was a sample survey using a self-report questionnaire. Regarding the level of burn out experienced by graduate psychology students, the results of the survey indicate that the students experience low levels of academic burn out. Regarding the level of stress experienced by psychology graduate students, the results show that participants experience moderate levels of idiosyncratic stress and moderate to high levels of situational stress. The analysis showed that there was no statistically significant difference in the means between males and females. Regarding the relationship between academic burnout and anxiety, Pearson r analysis showed that there is no correlation between the two concepts.